Ovarian torsion in adolescent - Hansda, Rosalin; Pandit, Mahima; Ghosh, Debmalya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Ovarian torsion is a gynaecological emergency which requires immediate surgical intervention for salvaging ovary and fertility. Ovarian torsions present with acute pelvic pain which is followed by autonomic reflex response (nausea, emesis and tachycardia). In this case report we are reporting a case of 19 years old female with acute pain abdomen and vomiting. On examination she had tenderness in lower abdomen which shifted more towards the left iliac fossa, ultrasound suggested an ovarian cyst of size 51×81×100 mm. Ovarian torsion was diagnosed and immediate laparotomy was done.